Conversion of the Industrial Area - Zaslavskaya, Polina (project baikal, 2018)
The article features the processes of renovation of the former industrial facilities on the territory of Irkutsk. It provides the examples of conversion of industrial zones in different European cities and in Moscow, as well as the examples of transformation of former industrial facilities of Irkutsk into art centers. The article presents the concept of the master plan for transformation of the former Central Heating and Power Plant-2 and the Tea-Packing Factory into a public cultural space.